Simulation of Energy Bands for Metal and Semiconductor Junction - Wut Hmone Kyaw; May Nwe Myint Aye (Journal La Multiapp, 2020)
This paper presents the metal-semiconductor band structure analysis for metal-oxide semiconductor field effect transistor (MOSFET). The energy bands were observed at metal-semiconductor and semiconductor-metal junctions. The simulation results show energy variations by using gallium-nitride (GaN) material. Gallium nitride based MOSFETs have some special material properties and wide band-gap. From the energy band, the condition of contact potential, conduction and valence band-edges can be analyzed. The computerized simulation results for getting the band layers are investigated with MATLAB programming language.